The Ways of Making the Power Transformer’s Transformation Coefficient More Precise - Kairys, A.; Kostrauskas, P. (Elektronika ir Elektrotechnika, 2004)
Presented the method of determination transformation coefficient of power transformer, when known distance between primary and secondary windings. Given dependency between magnetic fluxes and no-load voltages. Transformation coefficients are express as functions of magnetic fluxes (main and leakage) and no-load voltages. Formulas are received with estimation of magnetic leakage fluxes for calculation of the number turn windings of multi-wound transformer under given turn ratio with inaccuracy not exceeding ±0,5%. Presented physical model of multi-wound power transformer, which allow calculate a number of turns of secondary windings for defined transformation coefficient. The Results of the work can be used when designing power multi-wound transformer with specifically exact transformation coefficient. Ill. 2, bibl. 5 (in English; summaries in Lithuanian, English, Russian).